(untitled) (Research, Society and Development, 2026)
The journey from developing computational systems to their application in education requires a vision that integrates the rigor of code with pedagogical mediation in supporting Undergraduate Thesis (TCC) writing. The objective of this study is to present and analyze, in a conceptual and propositional manner, the architecture and functioning of the Digital Thesis Advisor, discussing its potential as an instrument of pedagogical mediation in academic writing. This is an applied, qualitative, and propositional study, characterized as a technological development research. The tool employs a Retrieval-Augmented Generation (RAG) architecture and client-side processing, ensuring that Artificial Intelligence responses are based exclusively on materials provided by the student and that data remains under the user’s control. The system was designed to explain and guide, offering pedagogical feedback at each stage of the work. It is concluded that articulating pedagogical mediation, Artificial Intelligence, and a lightweight architecture constitutes a viable path to broaden access to scientific writing in higher education.